The hidden hand and the license raj to An evaluation of the relationship between age and the growth of firms in India - Majumdar, Sumit K (Journal of Business Venturing, 2004)
The study that this article reports on considers the consequences of nationally variable macroinstitutional environments, and the implications of major alterations in such environments, on organizational level behavior and performance. Specifically, it examines the relationship between firm age and growth for a large sample of Indian firms using contemporary data. Firms are classified as falling into three specific categories: those incorporated, or born, prior to 1956; those incorporated between 1956 and 1980; and those incorporated after 1980. Each of these selected periods defines and denotes specific policy regimes affecting Indian industry. These policy regimes have been dictated by the national macroinstitutional environmental considerations that were in existence for the Indian economy. No significant relationship is established between the age variable and growth for firms incorporated prior to 1956, while a negative relationship is established between the age variable and growth for firms incorporated between 1956 and 1980. These were the years when the command and control industrial policy regime, popularly known as the “license raj,” was in operation in India. Conversely, for firms incorporated after 1980 when market forces began to be encouraged, and the “hidden hand” started becoming visible to some degree in the Indian context, the age and growth relationship is established to be positive. The evidence suggests that entrepreneurial behavior is an extremely important feature of contemporary Indian industry. Recent anecdotes about Indian firms, particularly in the information technology sector, suggest that there has been a resurgence of industrial activity in the country. These beliefs are well borne out by the large-scale empirical analysis that this article reports on. The younger Indian firms, those which have not been imprinted by the taints of a command and control regime, are going to drive India's industrial progress forward. The “hidden hand” is alive and well in India. Conversely, older firms, which might seem to possess a stock of capabilities developed over time, are going to find that these are unlikely to be readily deployable in the future. Older firms might have had the attributes that led to corporate success in an environment where rent seeking was the norm. In the present milieu, such abilities are not conducive to corporate progress. In particular, the “license raj” firms have no capability to succeed, as shown by the negative age and growth relationship. Additionally, the relationship between size and the growth of Indian firms is found to be negative. This suggests that a process of industrial fragmentation may be taking place in Indian industry, with small firms growing faster than larger firms and reducing the importance of larger firms in Indian industry. This has important implications for the future competitiveness of Indian industry.